Assessment of n-alkanes and acyclic isoprenoids (geochemical markers) in crudes: A case study of Iraq and Niger delta, Nigeria - C.A. Nwadinigwe; T.N. Alumona (Egyptian Journal of Petroleum)
This study was designed to determine the ratios of the isoprenoids and n-alkanes in an imported crude oil sample (Bassrah from Iraq) and four crude oil samples (Bodo, Bonny-Export, Escravos and Penningston) from the Niger Delta region of Nigeria to ascertain the levels of maturity and as an indicator of the depositional environment of the crudes. The physical properties of the crudes: viscosity, density and °API gravity were also determined. Fractionation of the crudes was done using a new approach coded NAASAR, (n-alkanes, asphaltenes, aromatics and resins) comprising urea adduction followed by gas chromatographic analyses (for n-alkanes), n-heptane precipitation (for asphaltenes) and column chromatography (for resins). Results showed °API gravities Bassrah 28.03°, Bodo 31.89°, Bonny-Export 33.8°, Escravos 33.8°, and Penningston 33.8° indicating that Escravos, Penningston and Bonny-Export crudes are light crudes while Bodo and Bassrah crudes are medium crudes. The n-alkanes profiles of the five crudes were determined by gas chromatography ranged from n-C8H18 to n-C40H82 with total weight percent n-alkane yield Bassrah 11.2, Bodo 47.41, Bonny-Export 32.47, Escravos 5.58, Penningston 30.75 were obtained by urea adduction. The pristane to phytane ratios were computed, Bassrah 1.51, Bodo 1.48, Bonny-Export 1.08, Escravos 1.01 and Penningston 2.41. Isoprenoids to n-alkane ratios Pr/n-C17 in the same order of the crudes were 0.85, 0.83, 0.67, 0.65, 0.95 while phytane to n-C18 ratios were 0.61, 0.55, 0.62, 0.61 and 0.43. The results established the increasing level of maturity as obtained from Pr/n-C17 ratio in the order: Penningston < Bassrah < Bodo < Bonny-Export < Escravos. The result of Pr/Ph ratios show the same trend in the level of maturity. Penningston crude with Pr/Ph ratio 2.41 shows that the crude is deposited in fluviomarine and coastal swamp environment while Bassrah, Bodo, Bonny-Export and Escravos crudes indicate aquatic depositional environment (anoxia) condition. Keywords: Assessment, n-Alkanes, Acyclic isoprenoids, Pristane, Phytane, Maturity